MODERN APPROACHES FOR FORMATION OF YOUTH INTEREST IN PHYSICAL CULTURE AND SPORTS - Shkola, Olena Mykolaivna; Lesnikov, Yurii Olehovych (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
Physical education is an integral part of the educational process. The article states the search for effective approaches to grafting young interest to exercise physical culture and sports, introduces the use of the latest technologies in the system of physical education.